Avaliação da atividade antinociceptiva de Gymneia platanifolia (Lamiaceae) e Cumarinas isoladas da Polygala boliviensis (Polygalaceae) em modelos experimentais de dor - Silva, Bruno Cerqueira da (2024)
The objective of this study was to characterize and evaluate the antinociceptive activity of the methanolic extract (EMGP) and essential oil (OEGP) obtained from Gymneia platanifolia (leaves, stem and flowers). This study also evaluated the antinociceptive activity and in silico predictions of two compounds isolated from Polygala boliviensis, polygalene (POLI) and auraptene (AURA). OEGP was obtained by hydrodistillation for 3h, with 22 compounds detected, mainly consisting of spathulenol (31%) and caryophyllene oxide (10%). EMGP was obtained by maceration with methanol. In in vivo tests, OEGP, EMGP, POLI and AURA were administered to mice, showing action against hypernociception (abdominal contortions induced by acetic acid, formalin and arthritis induced by zymosan). However, the treatments did not change the response threshold to thermal stimulation in the hot plate test, indicating the absence of central action. Molecular docking routines were performed with the enzymes cyclooxygenase 1 and 2 (COX-1 and COX-2), myeloperoxidase (MPO), c-Jun N-Terminal Protein Kinase 1 (JNK1), NF-kappaB (NF-κB) and MAP kinase ERK2 (ERK2) to evaluate the pattern of intermolecular interactions with POLI and AURA. The docking showed that the compounds indicate a relevance of hydrophobic interactions, hydrogen bonds and salt bridges, important for molecular recognition in the active site of enzymes. Our results demonstrate important antinociceptive activity of EMGP, OEGP, POLI and AURA in animal models of pain, possibly involving peripheral pathways of the inflammatory cascade. The molecular docking technique identified affinity of POLI and AURA for COX-1, COX-2, MPO, JNK1, NF-κB and ERK2.